2019
DOI: 10.1007/s12144-019-00216-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and cyberchondria: The mediation effects of health anxiety and obsessive–compulsive symptoms in a community sample

Abstract: Cyberchondria refers to the excessive and repeated searching for medical information on the Internet and may be considered as health-related problematic Internet use. Previous findings indicated that cyberchondria is positively associated with health anxiety and obsessive-compulsive symptoms. Also, research suggests that excessive or problematic Internet use as well as health worries and compulsive behaviors are present among individuals with low self-esteem. This study sought to examine: (1) the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 83 publications
(164 reference statements)
3
47
1
4
Order By: Relevance
“…The correlations between cyberchondria and OCD symptoms have similarly been robust and ranged from 0.38 to 0.56 [14,17,21,22] for the total scores on the Dimensional Obsessive-Compulsive Scale. When the correlations were calculated for scores on the subscales of the Dimensional Obsessive-Compulsive Scale, they were lower (rs = 0.21-0.44) [22,29], as were the correlations with scores on the subscales of the Maudsley Obsessive-Compulsive Inventory (rs = 0.27-0.40) [30].…”
Section: Relationships Between Cyberchondria and Other Constructsmentioning
confidence: 92%
See 1 more Smart Citation
“…The correlations between cyberchondria and OCD symptoms have similarly been robust and ranged from 0.38 to 0.56 [14,17,21,22] for the total scores on the Dimensional Obsessive-Compulsive Scale. When the correlations were calculated for scores on the subscales of the Dimensional Obsessive-Compulsive Scale, they were lower (rs = 0.21-0.44) [22,29], as were the correlations with scores on the subscales of the Maudsley Obsessive-Compulsive Inventory (rs = 0.27-0.40) [30].…”
Section: Relationships Between Cyberchondria and Other Constructsmentioning
confidence: 92%
“…The concept of cyberchondria was developed on the basis of its hypothesized relationships with health anxiety and hypochondriasis. Many studies [11,12,14,[17][18][19][20][21][22][23][24][25][26] have confirmed moderate to strong correlations between cyberchondria and health anxiety (rs ranging from 0.48 to 0.68, depending on the instrument used for the assessment of health anxiety). Only one study [13] found this correlation to be relatively weak (r = 0.23).…”
Section: Relationships Between Cyberchondria and Other Constructsmentioning
confidence: 99%
“…Cyberchondria has been strongly associated with a heightened health anxiety (Bajcar & Babiak, 2019; Bajcar, Babiak, & Olchowska‐Kotala, 2019; Barke, Bleichhardt, Rief, & Doering, 2016; Fergus, 2014; McMullan, Berle, Arnáez, & Starcevic, 2019; Norr, Albanese, Oglesby, Allan, & Schmidt, 2015; Starcevic, Baggio, Berle, Khazaal, & Viswasam, 2019) and PIU (Fergus & Spada, 2017; McElroy & Shevlin, 2014; Singh & Brown, 2014; Starcevic et al, 2019). Cyberchondria is also related to obsessive–compulsive disorder (OCD; Bajcar et al, 2019; Bajcar & Babiak, 2019; Fergus, 2014; Fergus & Russell, 2016; Fergus & Spada, 2018; Vismara et al, 2020). According to the reassurance‐seeking model of cyberchondria (Starcevic & Berle, 2013), cyberchondria is maintained by uncertainty embedded in OHR, intolerance of ambiguity and uncertainty, dilemmas about the trustworthiness of the sources of online health information, need for a “definitive” or “straightforward” explanation and difficulty coping with an abundance of information (“information overload”), especially if much of that information is conflicting or contradictory.…”
Section: Cyberchondriamentioning
confidence: 99%
“…They also assess the quality of online health services as much higher and show a wider tendency to self-medicate. Depending on the severity of a hypochondriacal disorder, it can have a significant impact on things such as work ability, coping with everyday life, self-esteem, or resilience [28,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%